Autochthonous Starter Effect on Microbiological, Physicochemical Characteristics, and Fatty Acids Content of Moroccan Goat’s Milk Cheese During Ripening - Said Zantar; Yousra Zantar; Mohamed Benicha; Amin Laglaoui; Ouiam EL GALIOU; Mounir Hassani Zerrouk (African and Mediterranean Agricultural Journal - Al Awamia)
The present study investigates the influence of different lactic strains on physicochemical and microbiological composition of goat cheese as well as on the fatty acid content. Four types of cheese were made from pasteurized goat's milk (batch A: control cheese prepared without the addition of ferment, batch B: made with a commercial ferment, batch C: L. lactis subs. Lactis + L. paracasei, and batch D: L. lactis diacetylactis + L. lactis lactis supsp lactis.). Dry extract, titratable acidity, pH, fat, and total nitrogen were determined at 1, 7, 14, 21, and 28 days; and fatty acids were analyzed using gas chromatography. Types of microbial counts determined were: Total aerobic mesophilic flora (TAMF), lactic acid bacteria (LAB), total coliforms (TC), and fecal coliforms (FC). The addition of ferments led to a significant increase in protein and fat contents. The significant decrease in pH in the batches with ferments contributed to improving hygienic quality. Free Fatty acid analysis revealed that the addition of ferments significantly increased the concentrations of monounsaturated and polyunsaturated fatty acids and significantly reduced saturated fatty acids.